PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BALAI BESAR TEKNOLOGI AERODINAMIKA, AEROELASTIKA DAN AEROAKUSTIKA BPPT INDONESIA - Dira Karlina; Yulies Herni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This research was conducted with the aim of knowing the effect of leadership style and work motivation simultaneously on employee performance at the Center for Aerodynamics Technology, Aeroelastic Aeroacoustics (BBTA3) Puspiptek Serpong-South Tangerang. The research method used is descriptive research with quantitative data analysis. The sampling technique used is Saturated Sample with a total sample of 66 respondents at the Center for Aerodynamics, Aeroelastics, Aeroacoustics Technology (BBTA3). Based on the results of data processing, it is known that leadership style affects employee performance with a significant rate value of 0.000 <0.05, then Ha1 is accepted and H01 is rejected. Work motivation has no effect on employee performance with a significant level value of 0.497 > 0.05, then H02 is accepted and Ha2 is rejected. The results of the simultaneous correlation test, leadership style and work motivation with employee performance are 0.678. The coefficient of determination value is 0.459. This means that leadership style and work motivation contribute 45.9%, while the remaining 54.1% is influenced by other variables outside this study.